Spatial Configuration & Management Street Vendors in Public Space - Sandhika, Rendy Rian; Sholihah, Arif Budi; Yuli, Nensi Golda (Journal of Architectural Design and Urbanism, 2024)
Street vendors contribute to meeting people's needs, but not by their presence in public spaces. This dynamic is important, and attention is paid to street vendors' spatial configuration and management in public spaces. This study aims to learn more about the spatial configuration & management of street vendors in public spaces. The method used is a Systematic Literature Review (SLR), with a search and analysis related to the spatial configuration and management of street vendors in public spaces in 35 journals in the last 10 years. This process shows that the spatial configuration and management of street vendors influence the dynamics of public spaces, creating diverse economic and social activities. So, the existence of a spatial configuration, and comprehensive management of street vendors in public spaces will minimize management problems in public spaces. This contribution provides knowledge for sustainable urban planning and the development of policies that consider spatial configurations to accommodate the management of street vendors in public spaces.